A retrospective analysis of growth hormone therapy in children with Schaaf-Yang syndrome - Hebach, Nils R.; Caro, Pilar; Martin-Giacalone, Bailey A.; Lupo, Philip J.; Marbach, Felix; Choukair, Daniela; Schaaf, Christian P. (Clinical genetics, 2021)
Short stature is a common phenotype in children with Schaaf-Yang syndrome (SYS). Prader-Willi syndrome (PWS) and SYS share several phenotypic features including short stature, muscular hypotonia and developmental delay/intellectual disability. Evidence exists that similar to PWS, growth hormone (GH) deficiency may also be a feature of SYS. Recombinant human GH (rhGH) therapy has been approved for PWS, but the effects of rhGH therapy in individuals with SYS have not yet been documented. This retrospective, questionnaire-based study analyzes the prevalence of rhGH therapy in children with SYS, the effects of rhGH therapy on anthropometric measures, and parental perception of the treatment. Twenty-six individuals with SYS were sent a clinical questionnaire and a request for growth charts. We found a significant increase in height z-score (p* = 0.04) as well as a significant decrease in body mass index 6 months after rhGH therapy initiation (p* = 0.04). Furthermore, height z-scores of the treated group (mean z-score = −1.00) were significantly higher than those of the untreated group (mean z-score = −3.36, p = 0.01) at time of enrollment. All parents reported an increase in muscle strength and endurance, and several families noted beneficial effects such as improved cognition and motor development.